The use of differentiated education strategy and its impact on mathematical thinking among fifth graders (Journal of the College of Basic Education, 2022)
The aim of the current research is to find out (the use of differentiated education strategy and its impact on mathematical thinking among fifth grade students).In order to achieve the aim of the research, the following hypothesis was formulated:There is no statistically significant difference at the level (0.05) between the mean scores of the students of the experimental group (who study using the differentiated learning strategy) and the scores of the students of the control group (who study in the usual way) in the mathematical thinking test as a whole.Seven sub-hypotheses were derived from it according to the areas of mathematical thinking (induction, conclusion, generalization, expression by symbols, guessing, modeling, logical-formal thinking).